Parasite Genotype Is a Major Predictor of Mortality from Visceral Leishmaniasis - Cooper Alastair Grace; Kátia Silene Sousa Carvalho; Mayara Ingrid Sousa Lima; Vladimir Costa Silva; João Luís Reis-Cunha; Matthew J. Brune; Sarah Forrester; Conceição de Maria Pedrozo e Silva de Azevedo; Dorcas Lamounier Costa; Doug Speed; Jeremy C. Mottram; Daniel Jeffares; et al. (2022)
Visceral leishmaniasis (VL) is a potentially fatal disease caused mainly by Leishmania infantum in South America and Leishmania donovani in Asia and Africa. Disease outcomes have been associated with patient genotype, nutrition, age, sex, comorbidities, and coinfections. In this study, we examine the effects of parasite genetic variation on VL disease severity in Brazil. We collected and sequenced the genomes of 109 L. infantum isolates from patients in northeastern Brazil and retrieved matching patient clinical data from medical records, including mortality, sex, HIV coinfection, and laboratory data (creatinine, hemoglobin, and leukocyte and platelet counts). We identified genetic differences between parasite isolates, including single nucleotide polymorphisms (SNPs), small insertions/deletions (indels), and variations in genic, intergenic, and chromosome copy numbers (copy number variants [CNVs]). To describe associations between the parasite genotypes and clinical outcomes, we applied quantitative genetics methods of heritability and genome-wide association studies (GWAS), treating clinical outcomes as traits that may be influenced by parasite genotype. Multiple aspects of the genetic analysis indicate that parasite genotype affects clinical outcomes. We estimate that parasite genotype explains 83% chance of mortality (narrow-sense heritability [h 2] = 0.83 6 0.17) and has a significant relationship with patient sex (h 2 = 0.60 6 0.27). Impacts of parasite genotype on other clinical traits are lower (h 2 # 0.34). GWAS analysis identified multiple parasite genetic loci that were significantly associated with clinical outcomes; 17 CNVs were significantly associated with mortality, two with creatinine, and one with bacterial coinfection, jaundice, and HIV coinfection, and two SNPs/indels and six CNVs were associated with age, jaundice, HIV and bacterial coinfections, creatinine, and/or bleeding sites. Parasite genotype is an important factor in VL disease severity in Brazil. Our analysis indicates that specific genetic differences between parasites act as virulence factors, enhancing risks of severe disease and mortality. More detailed understanding of these virulence factors could be exploited for novel therapies. IMPORTANCE Multiple factors contribute to the risk of mortality from visceral leishmaniasis (VL), including, patient genotype, comorbidities, and nutrition. Many of these factors are influenced by socioeconomic biases. Our work suggests that the virulence of the infecting parasite is an important risk factor for mortality. We pinpoint some specific genomic markers that are associated with mortality, which can lead to a greater understanding of the molecular mechanisms that cause severe VL disease, to the identification of genetic markers for virulent parasites, and to the development of drug and vaccine therapies.